Heating versus Cooling in Galaxies and Clusters of Galaxies: Proceedings of the MPA/ESO/MPE/USM Joint Astronomy Conference held in Garching, Germany, 6 - 11 August 2006 - Böhringer, Hans (Springer, 2007)
This volume documents recent developments that have advanced our understanding of the heating and cooling mechanisms in galaxies and galaxy clusters. Chapters detail results from multi-wavelength observations and advances in numerical hydrodynamical simulations. An additional section covers new research findings on feedback and self-regulatory mechanisms during cosmic structure formation in general and in galaxy formation in particular.
Includes bibliographical references
Keywords: Konferenzschrift -- 2006 -- Garching, München; Konferenzschrift -- München, 2006 -- Garching; Galaxienhaufen; Galaxie